Effectiveness of Internet- and mobile-based psychological interventions for the prevention of mental disorders: a systematic review and meta-analysis protocol. Issue 1 (December 2016) - Sander, Lasse; Rausch, Leonie; Baumeister, Harald
Abstract Background Despite progress in developing technologies for health promotion and disease treatment, mental disorders remain highly prevalent. In light of the associated personal and societal burden, primary prevention of new onset disorder can be seen as a primary challenge for health care systems and society. Internet- and mobile-based interventions (IMIs) are a promising approach to scale up preventive measures to a population level. The present protocol describes the rationale and design of a systematic review on the effectiveness of IMIs for the prevention of mental disorders. Methods/design A systematic literature search (MEDLINE, PsycINFO, CENTRAL) will be conducted. Keywords will target the topics "prevention", "mental disorders", and "Internet and mobile-based interventions". Studies eligible for inclusion will be retrieved, and data will be extracted and evaluated (design, population, outcomes, sample size, duration of intervention and follow-up, drop-out rate) by two independent researchers. Quality of evidence will be assessed, and results will be synthesized qualitatively and pooled meta-analytically when outcome data are comparable in terms of endpoints, assessments, and target disorders. Discussion Prevention of mental disorders is one of the major emerging global health challenges. This review and meta-analysis will contribute to our understanding of the potential role for IMIs to help address this challenge. Systematic review registration PROSPEROCRD42015026781